Antwerp City Wastescapes. Historic interplays between waste & urban development. - Marin, Julie; De Meulder, Bruno (International Planning History Society Proceedings, 2016)
This paper analyses waste management and the production of space over time in the city of Antwerp, Belgium. By reconstructing how shifting waste practices simultaneously reshape our urban environments at multiple scales, this paper also articulates historic interplays between waste management, urban development and planning practices. Benefiting from available waste processes and materials is a practice that disappeared during industrialisation scale jumps and more linear processes of urbanisation and consumption indeed dominate the current practices. But cities like Antwerp are rethinking these resource consumptive processes and orienting their policies towards what is generally labelled as a resource independent ‘circular economy’. In order to be resilient for climate change, Antwerp’s centralized and heavily engineered and stressed waste collection and treatment installations of the last century require revision, if not systemic redefinition. After a century of dumping on peripheral locations, bottom-up initiatives such as repair cafés, zero waste shops, green schools and even supermarkets are changing the cultural appreciation of ‘waste’ in Antwerp by pulling ‘waste practices’ back into the city and activating social community spaces. What can we learn from the historic interplays between waste and urban development in Antwerp at the eve of Antwerp’s next –circular- waste geography?